Unlocking the genetic diversity of Indian turmeric (Curcuma longa L.) germplasm based on rhizome yield traits and curcuminoids - Dudekula, Mastan Vali; Kandasamy, Venkatesan; Balaraman, Senthamizh Selvi; Selvamani, Selva Babu; Muthurajan, Raveendran; Adhimoolam, Karthikeyan; Manoharan, Bharani; Natesan, Senthil (Frontiers in Plant Science, 2022)
Turmeric is an important commercial crop widely grown in Asia due to its pharmacological and nutritional value. India is the center of turmeric diversity and many germplasm have good rhizome yield, varying curcuminoids content and are well-adapted to various agro-climatic zones. In the present study, we unravel the diversity among 200 Indian turmeric germplasm based on rhizome yield traits and curcuminoids content. We also performed clustering and correlation studies to group the germplasm and to observe the relationship between the traits. Results revealed the presence of large variability among turmeric germplasm including the major traits such as yield (24.77 g p-1 to 667.63 g p-1), dry recovery percentage (13.42 % to 29.18 %), curcumin (0.41 % to 2.17 %), demethoxycurcumin (0.38 % to 1.45 %), bisdemethoxycurcumin (0.37 % to 1.24 %) and total curcuminoid content (1.26 % to 4.55 %). The superior germplasm identified for curcuminoids content were as follows; curcumin (CL 157 – 2.17 % and CL 272 – 2.13 %), demethoxycurcumin (CL 253 – 1.45 % and CL 157 – 1.31 %), bisdemethoxycurcumin (CL 216 – 1.24 % and CL 57 – 1.11 %) and total curcuminoid content (CL 157 – 4.55 % and CL 272 – 4.37 %). Clustering based on dendrogram grouped 200 genotypes into seven clusters. Among seven clusters, the maximum numbers of genotypes were grouped into cluster II while cluster VII showed maximum mean value for the majority of the traits. Correlation analysis revealed a significant relationship between the traits where the total curcuminoid content is in significant positive correlation with the primary rhizome core diameter and length of the secondary rhizome. The selection of these particular traits may result in the identification of genotypes with high total curcuminoid content. Taken together, it is the first report on the large screening of turmeric germplasm for variation in the rhizome yield traits and curcuminoids content. The genetic diversity revealed in this study could be useful for turmeric crop improvement programs to develop new varieties with high rhizome yield coupled with high curcuminoids content.